1977
DOI: 10.3382/ps.0561468
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Starvation on Antibody Production of Chicks

Abstract: The effect of 24 and 48 hours of food and water deprivation on ascorbic acid, liver, leukocyte counts and internal lymphoid organ weights of crossbred chicks was examined. Starvation caused an increase in plasma ascorbic acid level, a significant decrease in leucocyte count in peripheral blood, significant loss in body weight and a profound loss in liver, bursa of fabricius, spleen and thymus weights. Deprived chicks were I.V. injected with Escherichia coli dead bacteria and sheep red blood cells at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 9 publications
1
8
0
2
Order By: Relevance
“…It is known that stress conditions affect the immune system and cause immunosuppression [9,16,24] through involution of lymphoid organs [3,4,21], possibly mediated by increased activity of the pituitary adrenocortical axis [8,21,25]. It appears that stress situations act by enhancing virus replication in lymphocytes as shown in the spleen of stressed mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that stress conditions affect the immune system and cause immunosuppression [9,16,24] through involution of lymphoid organs [3,4,21], possibly mediated by increased activity of the pituitary adrenocortical axis [8,21,25]. It appears that stress situations act by enhancing virus replication in lymphocytes as shown in the spleen of stressed mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, starvation [3], cortisol injection [21] cold or isolation stress [4] can cause involution of lymphoid organs such as thymus, spleen and lymph nodes through activation of the pituitary adrenocortical axis [25,8]. Further, interferon production is suppressed in stress situations [ 14], and T-helper lymphocyte levels are reduced under various types of stress [ 17,24].…”
Section: Introductionmentioning
confidence: 99%
“…Perek and Sulman (1945) reported an increase in basal metabolic rate (BMR) and Brake and Thaxton (1979a) noted that body temperature was elevated during a forced molt in SCWL hens. A 48 hr period of food and water deprivation has also been reported to elicit symptoms of physiological stress in young birds (Ben Nathan et al, 1977). Glazener and Jull (1946) reported that thiouracil retarded the rate of feather loss during a natural molt.…”
Section: Introductionmentioning
confidence: 99%
“…Dolayısıyla yaşama gücünün cinsiyet veya beslenme şeklinden etkilenmediği söylenebilir. Bu sonuç, kısıtlı besleme gruplarında yaşama gücünün yüksek olduğunu bildirilen kaynaklardan (11,24,38) farklıdır. Sıcak ve soğuk karkas randımanı tüm gruplarda CA'a paralellik göstererek erkeklerde yüksektir (19,26).…”
Section: Tartışma Ve Sonuçunclassified